Expression and Clinical Significance of CXCR5 and LAG‐3 on Peripheral Blood CD8 + T Cells in Patients With Diffuse Large B‐Cell Lymphoma - Xi‐Zhe Guo; Ya‐Fei Guo; Shi‐Xin Wu (Kaohsiung Journal of Medical Sciences)
ABSTRACT Diffuse large B‐cell lymphoma (DLBCL) exhibits substantial biological and clinical heterogeneity. This study investigated the expression and prognostic implications of C‐X‐C chemokine receptor type 5 (CXCR5) and lymphocyte activation gene‐3 (LAG‐3) on peripheral blood CD8+ T cells in patients with DLBCL. A total of 71 DLBCL patients and 71 healthy controls were enrolled. The expression levels of CXCR5 and LAG‐3 on peripheral blood CD8+ T cells were assessed and analyzed for their impact on 5‐year progression‐free survival (PFS) and overall survival (OS). Results revealed significantly elevated CXCR5 and LAG‐3 expression levels in DLBCL patients compared to controls. CXCR5 expression correlated with lactate dehydrogenase (LDH) levels, extranodal involvement, Ann Arbor stage, and International Prognostic Index (IPI) scores, while LAG‐3 expression was associated with Eastern Cooperative Oncology Group (ECOG) scores, number of extranodal sites, bone marrow involvement, Ann Arbor stage, and IPI scores. Multivariate analysis identified advanced age, Ann Arbor stage III‐IV, and elevated CXCR5 and LAG‐3 expression as independent risk factors for poorer 5‐year PFS and OS. Furthermore, patients with higher CXCR5 and LAG‐3 expression levels demonstrated significantly reduced 5‐year PFS and OS rates. In conclusion, elevated CXCR5 and LAG‐3 expression on peripheral blood CD8+ T cells plays a pivotal role in DLBCL progression and prognosis, making these markers potential therapeutic targets or prognostic indicators.